Smoking and sickness absence: a systematic review and meta-analysis - Troelstra, Sigrid A; Coenen, Pieter; Boot, Cécile RL; Harting, Janneke; Kunst, Anton E; van der Beek, Allard J (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVES ': 'Evidence on the effect of smoking on sickness absence could guide workplace smoking cessation interventions and encourage employers to promote smoking cessation among their employees. This systematic review and meta-analysis aimed to summarize evidence on the association between smoking and sickness absence and determine whether there are differences in this association for study design, methodology, and sample characteristics. ' ' METHODS ': 'We searched for studies that reported on smoking status and sickness absence, used empirical data, were published in a peer-reviewed journal in the last 25 years, and written in English. We conducted pooled analyses in which uni- and multivariate generalized linear regression models were applied. ' ' RESULTS ': 'After screening 2551 unique records, 46 articles from 43 studies were included, of which 33 studies (with 1 240 723 participants) could be included in the pooled analyses. Smoking was associated with an 31% increase in risk of sickness absence compared to non-smoking (95% confidence interval (CI) 1.24–39). We did not find statistically significant different effect sizes for study location, gender, age, occupational class, study design, assessment of sickness absence, short- versus long-term sickness absence, and adjustment for relevant confounders. Furthermore, smoking was associated with 2.89 more sickness absence days per year compared to non-smoking (95% CI 2.08–3.70). ' ' CONCLUSIONS ': 'We found robust evidence showing that smoking increases both the risk and number of sickness absence days in working populations, regardless of study location, gender, age, and occupational class. Encouraging smoking cessation at the workplace could therefore be beneficial for employers and employees.
Keywords: absenteeism; meta-analysis; meta-regression analysis; review; sick leave; sickness absence; smoker; smoking; systematic review; tobacco